CORPORATE GOVERNANCE, FINANCIAL REPORTING QUALITY, AND FIRM PERFORMANCE: EVIDENCE FROM INDONESIA - Maria Natalia; Yunita Christy; Verani Carolina; Revaldo Farrel Witanto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The aim of this research is to examine the connection between corporate governance, the dependability of financial statements, and the functioning of non-financial corporations listed on the Indonesia Stock Exchange during the years 2019 to 2021. This research draws on the findings of Khatib & Nour (2021), which indicated that an increase in board size significantly improves firm performance. Moreover, it cites the research conducted by Sohail & Aziz (2019), demonstrating that quality of financial reporting affects corporate performance. Utilizing the ASEAN CG Scorecard as a benchmark for corporate governance sets this research apart from earlier studies, as do the selected sample and the time frame of the research. This research contributes to the current literature on corporate governance criteria by employing the ASEAN CG Scorecard. Instead of concentrating on a limited range of indicators, this approach aims to deliver a comprehensive overview of corporate governance practices. Furthermore, since it is based on OECD standards, the ASEAN CG Scorecard is expected to enhance investor trust in publicly traded firms. The goals of this research are to assess whether effective governance influences corporate performance and to evaluate if the quality of financial reporting impacts overall corporate success.